Pelatihan Memanfaatkan Limbah Rumah Tangga Menjadi Barang yang Bernilai Ekonomis pada Kelompok Karang Taruna di Balekambang, Jakarta Timur (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2021)
The purpose of this community service activity to provide skills training in utilizing household waste into goods of economic value and worth marketable. The training was conducted at Karang Taruna RT 003 RW 05 Balekambang Village, Condet, East Jakarta. The target of this activity plan is one of tridarma universities, namely community service. The method used by Indraprasta University lecturer team in this activity is to provide skills training by presenting and direct practice activities by teaching some skills to make various decorations and items applied with fanel cloth so that it can have economic value to 10 (ten) teenagers Karang Taruna RT 003/05 Kel. Balekambang Kec. Kramat Jati, East Jakarta as a provision for entrepreneurship later.